Toxicity of fermented soybean product (cheonggukjang) manufactured by mixed culture of Bacillus subtilis MC31 and Lactobacillus sakei 383 on liver and kidney of ICR mice - Lee, Young-Ju (Korean Association for Laboratory Animal Science, 2014)
To investigate the toxic effects of cheonggukjang (CKJ) manufactured using mixed cultures of Bacillus subtilis MC31 and Lactobacillus sakei 383 on the liver and kidney of ICR mice, an alteration on the related markers including body weight, organ weight, urine composition, liver pathology and kidney pathology were analyzed after oral administration at dosage of 25, 50 and 100 mg/kg body weight/day of CKJ for 14 days. Any significant toxicity was not observed on the body and organ weight, clinical phenotypes, urine parameters and mortality in the CKJ-treated group compared with the vehicle-treated group. Also, liver toxicity analysis revealed no significant increase in alkaline phosphatase (ALP), alanine aminotransferase (ALT), aspartate aminotransferase (AST) or lactate dehydrogenase (LDH) in response to CKJ. Additionally, the specific pathological features induced by most toxic compounds were not observed upon liver histological analysis. Furthermore, kidney toxicological analysis revealed that blood urea nitrogen (BUN) and the serum creatinine (Cr) levels and pathological features on histological sections did not differ significantly between the vehicle- and CKJ-treated groups. Overall, these results suggest that CKJ does not induce any specific toxicity in liver and kidney organs of ICR at dose of 100 mg/kg body weight/day as no observed adverse effect level (NOAEL).